HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG PENCEGAHAN DIARE DENGAN KEJADIAN DIARE PADA BATITA DI POSYANDU MAWAR XII WILAYAH KERJA PUSKESMAS BALOI PERMAI KOTA BATAM - Sihombing, Sarmauli Franshisca; Mariyana, Mariyana (Universitas Batam, 2020)
Diarrhea is a disease characterized by an increase in the frequency of defecation more than usual (3 or more per day) accompanied by changes in the shape and consistency of the patient's stool. According to the records of the Baloi Permai Health Center in Batam City, the number of toddlers who experienced diarrhea from the survey conducted by the researcher was 13 mothers who visited to check their children at the Baloi Permai Health Center in Batam City. there are 74 children under five. This study aims to determine the relationship between the mother's level of knowledge about prevention of diarrhea with the incidence of diarrhea in toddlers at the Baloi Permai Posyandu, Batam City. The type of research used is an Analytical Survey with a Cross Sectional approach, which was conducted at the Baloi Permai Posyandu, Batam City. The population in this study were toddlers aged 1 - 3 years. Sampling using perposive sampling technique, the number of samples was 36 toddlers in the Baloi Permai posyandu Batam City in 2015. Univariate results, Mother's knowledge about diarrhea prevention showed that more than half of mothers had less knowledge about preventing diarrhea in toddlers (69, 4%). The incidence of diarrhea in toddlers at the Posyandu Baloi Permai is more than half without diarrhea (58.3%). The results of the bivariate test, there is a significant relationship between mother's knowledge about prevention of diarrhea with the incidence of diarrhea in toddlers at Posyandu Baloi Permai Batam City in 2015 with p value = 0.025 <0.05, with an Odd Ratio value of 0.146. So it can be concluded that there is a significant relationship between mother's knowledge about diarrhea prevention and the incidence of diarrhea in toddlers at Posyandu Baloi Permai Batam City with p value = 0.025 <0.05.